Necessidades humanas básicas das pessoas em tratamento quimioterápico na pandemia Covid-19 - Ferreira, Poliana Martins (2021)
In recent decades, cancer has become a global public health problem. The diagnosis and treatment of cancer affects the biological, social and spiritual psychological dimensions. The current COVID-19 pandemic is causing damage, especially for those who are at risk, such as people undergoing chemotherapy. The immunosuppression caused by cancer and its treatment make these people have changes in their lives and relationships. Therefore, this scenario of social isolation caused by COVID-19 can affect the lives of these people in the biopsychosocial and spiritual dimensions, that is, the basic needs proposed by Abraham Maslow. General Objective: To analyze the basic needs of people undergoing chemotherapy at an Oncology Center in the south of Minas Gerais during the COVID-19 pandemic. Methodology: This is a descriptive- analytical, cross-sectional study with a quantitative approach, carried out at the Centro de Oncologia de Alfenas, MG. The convenience sample consisted of 105 participants; Sociodemographic and clinical information was extracted from medical records and Maslow's basic human needs instrument was subsequently applied via telephone call. Results: There was a predominance of females (58); age group: 60 years or older (63); married or living with a partner (61); profession: self-employed (37); residence (79) in other cities; (43) have elementary education; use tobacco (23) and alcohol (18); breast tumor (39), followed by urogenital tumors (21); surgery (71) adjuvant chemotherapy (40). The averages of the domains of basic human needs ranged from 6.29 to 8.53 and the values of standard deviations are relatively close, ranging from 2.03 to 2.94 units. Shapiro-Wilk tests were used to verify if the data present a normal distribution; Spearman's correlation coefficient to verify the correlation between variables, Cronbach's Alpha test to verify the consistency of the instrument and the Kruskal- Wallis test to test if there were differences between the sums observed in each domain, considering the categories of the variables sex, age, marital status and diagnosis, all considering p less than or equal to 0.50. Conclusion: The basic needs of people undergoing chemotherapy treatment in an Oncology Center in the South of Minas Gerais during the COVID-19 pandemic, evaluated by the constructed instrument, revealed that the averages of the domains ranged from 6.29 to 8.53, revealing that needs are affected and poorly met. The results of this research are expected to contribute to the advancement of scientific knowledge of the COVID 19 theme, to support the planning of care for cancer patients undergoing chemotherapy in times of a pandemic and to contribute to public policies for cancer patients. It should be noted that the instrument needs to be expanded, to increase the number of questions (variables in each domain).